The council of metropolitan see and its canonical basis an orthodox approach = Synode métropolitain et ses fondements canoniques : Perspective orthodoxe = Sinodo metropolitano e le sue basi canoniche : Prospettiva ortodossa - Mititelu, Cătălina (2019)
In this canonical study, the reader of the article will have an opportunity to become acquainted with an old European canonical-juridical institution, that is, the synodality, and, ipso facto, about its juridical regime. And, naturally, the reader can get acquainted more closely with the provisions of the canonical norms of the Eastern Church regarding the eparchial (metropolitan) synodality institution, and, ipso facto, with the issue of the regime of the synodality. Since the canonical bases of the synodality regime are foreseen in the canonical legislation of the first millennium, we had to make an hermeneutical analysis of its text, which showed us that, by resorting to ad fontes, we can also pave the way that would go towards the restoration of the unity of the two Christian worlds, namely, Pars Orientis and Pars Occidentis.
Le lecteur de cette étude aura l’occasion de se familiariser avec l’ancienne institution canonique et juridique européenne, c’est-à-dire la synodalité, notamment avec les dispositions des normes canoniques de l’Église d’Orient concernant l’institution éparchiale (métropolitaine) de la synodalité et, ipso facto, avec la question du système synodal. Comme les fondements canoniques du système synodal sont inclus dans la législation canonique du premier millénaire, nous avons dû faire une analyse herméneutique de son texte, ce qui nous a montré qu’en nous référant à ad fontes, nous pouvons aussi ouvrir une voie qui conduira à la restauration de l’unité des deux mondes chrétiens, c’est-à-dire de Pars Orientis et Pars Occidentis.
Il lettore di questo studio avrà l’opportunità di conoscere l’antica istituzione canonica e giuridica europea, cioè la sinodalità, e particolarmente le disposizioni delle norme canoniche della Chiesa d’Oriente relative all’istituzione eparchiale (metropolitana) della sinodalità e, ipso facto, la questione del sistema sinodale. Poiché le basi canoniche del sistema sinodale sono incluse nella legislazione canonica del primo millennio, abbiamo dovuto fare un’analisi ermeneutica del suo testo, il che ci ha mostrato che, facendo riferimento ad ad fontes, possiamo anche aprire una strada conducente al ripristino dell’unità dei due mondi cristiani, e cioè Pars Orientis e Pars Occidentis.
Keywords: canonical legislation; canonical-juridical institutions; the ecumenical councils; législation canonique; institutions de droit canoniques; synodes oecuméniques; legislazione canonica; istituzioni canoniche; sinodi ecumenici